Determinants of MSMEs Business Performance: The Role of Entrepreneurial Orientation, Business Management Capability, and Functional Business Capability - Paradisa Sukma; Muhammad Raihan Mubaraq; Victoria Kusumaningtyas Priyambodo (Program Studi Akuntansi Universitas Islam Lamongan, 2026)
This study examines the determinants of MSME business performance by investigating the roles of entrepreneurial orientation, business management capability, and functional capability. Using a quantitative associative approach, data were collected from 63 MSMEs in Mataram City, West Nusa Tenggara, Indonesia, and analyzed using PLS-SEM with SmartPLS. The results indicate that entrepreneurial orientation and business management capability have positive and significant effects on business performance, while functional capability has no significant effect. These findings highlight the importance of entrepreneurial orientation and managerial capability in improving MSME performance and competitiveness.